Pengelolaan Cold Storage 1.000 Ton Di Muara Baru Jakarta: Perspektif Ekonomi Kelembagaan Baru (Forum Agribisnis, 2024)
Fish cold storage was built by the Ministry of Maritime Affairs and Fisheries in various regions as one of the implementations of the National Fish Logistics System policy, which aims to maintain the availability of fish for industrial raw materials and domestic consumption. The cold storage of 1,000 tons was established to become a role model for the government's buffer stock facility in the Jakarta area. However, its implementation is still experiencing obstacles because its use is not optimal and has not attracted the interest of fisheries players in the broader scope. The research objective is to examine the institutional system implemented in managing cold storage of 1,000 tons from a business perspective. The research uses a case study method in government cold storages located in Muara Baru, North Jakarta. The institutional analysis of cold storage management was analyzed descriptively and qualitatively using the New Institutional Economic Theory approach. The research results show that the institution of cold storage of 1,000 tons still needs to improve its management. The aspects that contribute most to the lack of business performance in cold storage are property rights and, flexibility and adaptability. The implications that can be given are institutional improvements through 1) developing business models that are more tailored to user needs, 2) establishing bodies or institutions that are more authoritative in public services, 3) aligning incentives and building cooperation with a wider range of users, 4) implementation of standard procedures balanced with commitment to compliance from stakeholders and strong controls, 5) increased speed and flexibility of services and 6) competitive pricing.